GYY4137, a Hydrogen Sulfide Donor Modulates miR194-Dependent Collagen Realignment in Diabetic Kidney - John, AM Sashi Papu (Sci Rep, 2017)
The relationship between hydrogen sulfide (H(2)S), microRNAs (miRs), matrix metalloproteinases (MMPs) and poly-ADP-ribose-polymerase-1 (PARP-1) in diabetic kidney remodeling remains mostly obscured. We aimed at investigating whether alteration of miR-194-dependent MMPs and PARP-1 causes renal fibrosis in diabetes kidney, and whether H(2)S ameliorates fibrosis. Wild type, diabetic Akita mice as well as mouse glomerular endothelial cells (MGECs) were used as experimental models, and GYY4137 as H(2)S donor. In diabetic mice, plasma H(2)S levels were decreased while ROS and expression of its modulator (ROMO1) were increased. In addition, alteration of MMPs-9, −13 and −14 expression, PARP-1, HIF1α, and increased collagen biosynthesis as well as collagen cross-linking protein, P4HA1 and PLOD2 were observed along with diminished vascular density in diabetic kidney. These changes were ameliorated by GYY4137. Further, downregulated miRNA-194 was normalized by GYY4137 in diabetic kidney. Similar results were obtained in in vitro condition. Interestingly, miR-194 mimic also diminished ROS production, and normalized ROMO1, MMPs-9, −13 and −14, and PARP-1 along with collagen biosynthesis and cross-linking protein in HG condition. We conclude that decrease H(2)S diminishes miR-194, induces collagen deposition and realignment leading to fibrosis and renovascular constriction in diabetes. GYY4137 mitigates renal fibrosis in diabetes through miR-194-dependent pathway.